Paragesellschaften Imaginationen - Inszenierungen - Interaktionen in den Gegenwartskulturen - Hiergeist, Teresa; Bidmon, Agnes; Broders, Simone; Gerund, Katharina (De Gruyter, 2021)
In political and media debates, questions of societal homogeneity and heterogeneity are discussed using the keyword "parallel societies." The open concept of "parasocieties" in this volume sets itself in opposition to this reductionist gesture, thereby enabling a differentiated understanding of media reflections upon socio-political and societal interactions with diversity in the present day.